The Effect of Morale, Compensation and Work Conflict as Intervening Factors on Employee Performance: Case Study from Social Service Office of North Tapanuli Regency, Indonesia - Febrilian, Lamtiar; Sitorus, Sunday Ade; Lumbangaol, Vebry (Golden Ratio of Data in Summary, 2025)
This study aims to determine the effect of morale, compensation and work conflict as an intervening factor at the North Tapanuli Regency Social Service Office. In this study using a type of quantitative research, with the sampling technique in this study was saturated sampling with a sample of 58 respondents. This research method is non propability sampling using SmartPLS 4.0 software. The results of this study indicate that: (1) The Work Morale variable directly has no significant effect on Employee Performance with a significant level of 0.710> 0.05. (2) Work Morale variable directly has no significant effect on Work Conflict with a significant level of 0.401> 0.05. (3) Compensation variable directly has no significant effect on Employee Performance with a significant level of 0.687 > 0.05. (4) The Compensation variable does not directly have a significant effect on Conflict with a significant level of 0.028> 0.05 (5) The Work Conflict variable directly has a significant effect on Employee Performance This is evidenced by the significant results of 0.00> 0.05. (6) The Work Morale variable through Work Conflict as an Intervening variable directly has no significant effect on Employee Performance with a significant level of 0.408> 0.05. (7) Compensation variable through Work Conflict as an Intervening variable directly has a significant effect on Employee Performance with a significant level of 0.022 <0.05.Based on the results of simultaneous testing, this study is able to prove that there is (1) Work Morale variable directly has a positive but insignificant effect on Employee Performance, (2) Work Morale variable directly has a positive but insignificant effect on Work Conflict, (3) Compensation variable directly has a positive but insignificant effect on Employee Performance, (4) Compensation variable directly has a positive and significant effect on Work Conflict, (5) Work Conflict variable directly has a positive and significant effect on Employee Performance, (6) Work Morale variable through Work Conflict as an Intervening variable directly has a positive but insignificant effect on Employee Performance, (7) Compensation variable through Work Conflict as an Intervening variable directly has a positive and significant effect on Employee Performance.